Evaluation and Design of Mosque Financial Statements Based on ISAK 35 - Susanto, Nurhadi; Alamsyah, Ahmad Fahrudin (Gorontalo Accounting Journal, 2025)
The aim of this study is to analyze the financial report format presented by Masjid Besar Al-Jami' Khoirul Huda. This study also seeks to assess whether the financial report complies with ISAK 35 standards and to explore its benefits for the mosque's management. The research method used is a descriptive approach with a qualitative method. The findings of this study show that the financial report prepared by the mosque's treasurer only contains information about income and expenses, which complies with ISAK 35 standards. However, the report does not include a statement of financial position, which is an essential component of financial reporting according to accounting standards.